Wavelength Dependence of the Two Channels for Double Ionization of He in Intense Laser Field (Journal of Atomic and Molecular Sciences, 2017)
In this paper, we investigate the double ionization process of He for the shakeoff (SO) andcorrelated energy-sharing (CES) channels in intense laser field based on the intense-field many body S-matrixtheory (IMST). The wavelength dependence of the ionization rate from these two channels are analyzed andcompared with each other. According to our calculation, the CES channel dominants at long wavelengths(300-780nm), while the SO channel dominants at short wavelengths (20-200nm). The more interesting thingoccurs in the intermediate wavelength regime (200-300nm) where the contributions from the SO and CESchannels are comparable and may compete with each other.